Heparinized Saline Solution vs. Saline Solution (0.9% Sodium Chloride) for the Maintenance of Dorsal Pedal Arterial Catheter Patency in Dogs Undergoing General Anesthesia: A Pilot Study - Sasaki, Kazumasu; Paredes, Gonzalo Polo; Shiga, Takuya (Frontiers in Veterinary Science, 2020)
Heparin is widely used as an anticoagulant solution for maintaining arterial catheter patency. In humans, increasing evidence suggests that heparinized saline solution (HS) has no advantages over a saline (0.9% sodium chloride) solution (SS) in maintaining arterial catheter patency. To date, no studies have been conducted on the effectiveness of these solutions at maintaining arterial catheter patency in veterinary medicine. The objective of this pilot study was to determine the feasibility of a study and to report the treatment efficacy comparing HS and SS for the maintenance of the dorsal pedal arterial catheter patency during direct arterial blood pressure measurements in anesthetized dogs. Client-owned dogs undergoing abdominal surgery were allocated to two groups to receive either a continuous infusion of HS or SS through the dorsal pedal artery, and the arterial pressure waveform was monitored during general anesthesia. Our feasibility outcomes included the proportion of the screened veterinary patients that completed the study and the success rate of arterial catheter placement. The clinical outcomes were assessed by the number of catheter-flushing procedures, occlusion rate, the duration of the initial catheter-flushing procedures, and the duration of catheter occlusion. Of the 51 dogs screened, 41 (80.4%) completed the study. The success rate of arterial catheter placement in the HS and SS groups were 87.5% and 80.0%, respectively. There were no differences in the number of catheter-flushing procedures and occlusion rate between groups (28.6% vs. 20.0%, relative risk [RR]: 1.429, 95% confidence interval [CI]: 0.472–4.323, P = 0.719 and 14.3% vs. 15.0%, RR: 0.952, 95% CI: 0.217–4.179, P = 1.000, respectively). No differences were found in the probability of time to the initial catheter-flushing procedure and occlusion between groups assessed by the Kaplan-Meier method (P = 0.546 and P = 0.867, respectively). This study revealed the feasibility of a study comparing HS and SS for dorsal pedal arterial catheter patency during direct arterial blood pressure measurements in anesthetized dogs. Clinical outcome analyses were underpowered and thus, could not determine the meaningful differences in treatment efficacy between the groups. However, the information gained from this study provides insight for future study designs.